PROJECTS IN CORRESPONDENCE LEARNING - Axat Raxmatovich Azamatov (Bright Mind Publishing, 2025)
There is much discussion about the imperfection of the distance education system and the shallowness of students' knowledge. However, research on eliminating the shortcomings and improving this system remains insufficient. This article proposes the "Himoya" project, which recommends organizing blended learning in both real and virtual educational environments based on digitalization technologies. The project explores ways to enhance the distance education system by fully utilizing digitalization opportunities and provides relative recommendations.
Keywords: Digital technologies, educational activities, distance education, higher education, students, challenges, opportunities, Himoya project, knowledge monitoring.